A study of the student teaching program of the Northern Luzon Teachers College - Bonoan, Vicente A. 1935- ([Quezon City s.n.], 1969)
The author assessed the strengths and weaknesses of the student teaching program of the Northern Luzon Teachers College operating in Northern Luzon provinces of Abra, Apayao-Kalinga, Batanes, Cagayan, Ilocos Sur, Isabela, and Ilocos Norte in order to recommend measures of improvement.
Thesis (M.Ed.)--University of the Philippines
Typescript
Keywords: Northern Luzon Teachers College; Student teaching -- Luzon, Northern